LINKING PARTICIPATORY RURAL APPRAISALTOFOREST PROTECTION AND CONSERVATIONIN KATSINA STATE OF NIGERIA - Mohammed, S.; Danjuma, M.N. (European Scientific Journal, ESJ, 2014)
Globally, people and powers have diverse reasons of valuing and protecting forests. While some conserveforests for economic reasons, other for social, aesthetic and ecological benefits. In order to do that, approaches have been developed since time immemorial which were thought to be effective in managing forests but which constantly fail to meet objectives simply because of centralised governance of forest administration which mostly alienate local managers form the regime. In often cases, people who do not value the forest resources more than the local inhabitants implement forest decisions centrally thereby limiting investments and efforts of local actors as opposed to participatory practices. The participatory practices such as PRA unlike the classical approaches are more flexible a reason why they are borrowed into resources management from anthropology domain. They inherently have the propensity of integrating local actors in implementation and decision making. The aim of the study is to examine the linkages between participatory rural appraisal and its applicability in forest conservation in Katsina State. The main objective is to propose a tool for the inclusion of PRA tools in forestconservation of the state whichis as at now centrally governed from the office of the governor.